Dietary practices of children and adolescents residing in an area of Chakdaha Block, Nadia district, West Bengal - Sonali Ghosh; Semanti Das; Sarika Palepu; Farhad Ahamed (Journal of Family Medicine and Primary Care, 2024)
Background Childhood and adolescence are crucial developmental stages during the life course. They develop and establish lifelong dietary and lifestyle habits. Unhealthy food environments that influence the risk of obesity and other nutrition-related NCDs by affecting the dietary patterns. Assessment of dietary patterns and factors affecting them will help to provide targeted interventions to improve the same. Methods A community-based cross-sectional study was conducted among children aged more than 6 months and adolescents by interviewing their mothers regarding the dietary patterns. A two-stage sampling method was followed for selection of the participants. Results A total of 325 participants were interviewed. Dietary diversity (DD) was present in 55.4% of the participants. Children of mothers who were educated beyond middle school (aOR = 3.81 (1.87-7.73), P = 0.000) and children who stayed in a joint family (aOR = 1.73 (1.11-2.72) P < 0.05) had higher odds of having dietary diversity in their diet, after adjusting for age and sex. Fast food shop location (aOR = 0.14 (0.05-0.38), P value = 0.000) was found to have a significant association with fast food intake among participants. Conclusion Children and adolescents residing in the study area have a distinct dietary pattern compared to prevalent dietary practices in India. To improve dietary diversity of children and adolescents, maternal education, family dynamics, and community food environment, which include fast food and market locations, can be points of targeted interventions